Changes in the absorptive capacity of soils of Donbass degraded agroecosystems - D. V. Syshchykov; I. V. Agurova (Бюллетень Почвенного института им. В.В. Докучаева, 2023)
The aim of the work was to study the qualitative and quantitative composition of the soil-absorbing complex of degraded soils of agricultural land on the territory of the Donetsk People's Republic (DPR). The main tasks of the work were to study the amount of exchangeable bases, as well as the exchangeable calcium and magnesium of degraded soils. To study the soil cover of degraded agroecosystems, model plots were selected, located in the northern part of the Shakhterskiy region of the DPR, represented by gravelly chernozems unwashed and medium-washed. The site with steppe vegetation (ordinary medium-humus chernozem) was selected as the control variant. The results of studies of soil absorption capacity of agrocenoses in general indicate the development of degradation processes. The sum of the exchangeable bases of all studied soils is significantly reduced in comparison with the zonal soil, and the minimum values of the studied indicator, compared to the control, are recorded on slope areas of the fields (76.6–81.8% in relation to the control). On the fallow field, no statistically significant differences were found between the values of the sum of exchangeable bases compared to the control, which is most likely due to the lack of intensive agricultural exploitation and the application of mineral nutritive elements to the soil of this site. In the soils of almost all model sites (with the exception of the fallow field), the content of exchangeable calcium decreased by 27.4–42.7% compared to zonal soil. While studying the content of exchangeable magnesium, some regularities have been noticed, which are due to correlation with exchangeable calcium. Thus, the intensification of agricultural soil use resulted in an increased ratio of magnesium to calcium – on average to 1 : 3, while in the control it was 1 : 5. Such a transformation in the future can negatively affect the soilabsorbing complex and the soil as a whole, further loss of soil structure and a number of other negative consequences.